Ethnophysics Study of the Malige Traditional House: Identification of Physics Principles in Local Wisdom for Physics Education: Kajian Etnofisika Rumah Adat Malige: Identifikasi Prinsip Fisika dalam Kearifan Lokal untuk Pembelajaran Fisika - Awal Mulia Rejeki Tumanggor; Armanto; Megastin Massang Lumembang; Berton Maruli Siahaan; Daniel Jesayanto Jaya (Bestari: Jurnal Pendidikan dan Kebudayaan, 2026)
Local wisdom in the architecture of Malige reflects the intuitive understanding of the Buton people regarding principles of physics, making it compelling to study in the context of physics education. This study aims to identify the physics principles in the Malige Traditional House in Bau-Bau through an ethnophysics approach. The method used was descriptive qualitative, with data collection through observation, interviews, and documentation studies. The results reveal the application of rigid body equilibrium and force distribution concepts in nail-less wooden joints, fluid mechanics in the natural ventilation system, and force equilibrium on the inclined plane of the stairs. The study concludes that this local wisdom aligns with modern physics theory and holds potential as a source for meaningful contextual physics learning.